Plants Community Composition and Dynamism during Summer in Tehsil Takht-E-Nasrati Hills, District Karak, Pakistan (Global Journal of Science Frontier Research, 2013)
Plant life community structure is a key marker of long-term vegetation change in semi-arid ecosystems. In the present investigation overall 11 plant communities were recorded during summer. The number of plant species differs in different communities. As a whole in plains the Cenchrus-Zizyphus-Saccharum community was developed and composed of 36 species. There were 9 tree, 12 shrub and 15 herb species. The importance value contributed by three dominants species i.e., Zizyphus maurtiana, Aerua persica and Rhazya stricta was 63.34 while total importance value of 236.66 was provided by the remaining species. The contribution by tree was 47.76, shrubs (IV = 82.05) and herbs (IV = 170.20). The soil of the area had better calcium carbonate in the range of (12.3 -12.7 %), with soil pH (6.06 -8.13). The concentrations of P and K content were found in the range of (3.64-3.86 mg Kg-1) and (112-127 mg Kg-1). The EC was found in the range of (0.15-0.21 dS m-1). The soil texture was found from sandy clay to sandy clay loam. These results emphasize the continuous need for long-term ground-based ecological monitoring in conjunction with satellite-based monitoring of changes in plant life cover.
Keywords: altitudinal effect; community; plant life structure; life form and leaf size classes